UJ Students’ Attitude towards the Role of Social Media Platforms (Facebook and Twitter) in Spreading Political Culture and Knowledge - Al-Khaddam, Abdullah Falah Hazaa’ (Dirasat: Educational Sciences, 2023)
Objectives: The study aims to analyze the attitudes of students at the University of Jordan towards the role of social media platforms (Facebook and Twitter) in spreading political culture and knowledge. It also examines the factors that might influence their attitudes. Methods: This is a descriptive study that uses the survey method and relies on stratified random sampling. The study population consists of all UJ students (54.189) in the second semester of the academic year (2021-2022). The study sample consists of (375) male and female students. Results: The results show that UJ students’ attitudes towards the role of social media platfroms in spreading political culture and knowledge are highly positive. In addition, their attitudes do not vary according to differences related to gender, college, or year of study. Conclusions: The study recommends motivating university students to enrich the political content that is promoted on social media and to conduct more research on the level of political culture and knowledge among students in public and private Jordanian universities.